Pharmacological evaluation of cassia auriculata bark extract - MAHENDRA SHIRADKAR,; G. PAWANKUMAR,; KAPIL SHAH, (International Journal of Pharma and Bio Sciences, 2011)
This project was designed with the objective of investigating glucose lowering potential, anti-mutagenic activity and anti-fertility activity of Cassia auriculata bark extract in the diabetic animals. The albino rats were treated with methanolic extract. The extracts were found to posses promising anti-diabetic, antimutagenic and anti-fertility activities..